PENGARUH PEMANFAATAN PERPUSTAKAAN TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS X DAN XI PADA MATA PELAJARAN AL-QUR’AN HADIST DI MA AL-IMAROH - Auliannisa, Isnaini; H Mansyur, Masykur; Ulya, Neng (STAI Ihyaul Ulum Gresik, 2025)
This study aims to analyze the influence of the use of the school library on improving student learning outcomes in class X and XI in the Al-Qur'an Hadith subject at MA Al-Imaroh Kab. Bekasi. In this study, using primary data and using a questionnaire. The method used in this research uses a correlational method with a survey approach. The population in this study were students of class X and XI at MA Al-Imaroh Kab. Bekasi and as many as 79 students who became the research sample with simple random sampling technique. The results of the research on the linearity test found that there was a linear relationship between the school library utilization variable and the increase in learning outcomes in Al-Qur'an Hadith subjects (sig. 0.802 > 0.05). In the t test it was found that there was a significant effect of using the school library on increasing learning outcomes in Al-Qur'an Hadith subjects (sig. 0.000 <0.05). From the regression analysis, the effect is in the same direction, meaning that if the utilization of the school library increases by 1%, the variable of increasing learning outcomes in Al-Qur'an Hadith subjects will increase by 0.776. In the coefficient of determination (R Square) it was found that the effect of using the school library on increasing learning outcomes in Al-Qur'an Hadith subjects was 74.1%. The conclusion from this study is that there is a positive and significant influence on the use of the school library on improving the learning outcomes of class X and XI students in the Al-Qur'an Hadith subject at MA Al-Imaroh Kab. Bekasi.